(untitled) (Libellarium: journal for research in the field of information and related sciences, 2016)
The topic of this paper is to set the starting point for studying the history of Croatian emigrant journalism in Chile from the earliest period of the settlement of Croats until the end of 1914, including the dominant population group from Brač. It was primarily the economic migration, which was caused by economic changes in the society in general, and economic changes as a consequence of political movements. The immigrants had the need for organizing themselves in various societies in the new country, and they also had the awareness of their own nationality and language. The unusually rapid assimilation (already in the first generation) calls into question the viability and the need to preserve heritage. Immigrant newspapers edited and run by Brač emigrant journalists, most notably Ivan Krstulović and Luka Bonačić, with the newspaper Domovina from Punta Arenas, were in the current literature perceived almost exclusively in terms of political orientation and struggle. The aim of this paper is to show that the local newspaper Domovina reflected and recorded phenomena and events significant for the daily life of the community with the intention of preservation its identity from the perspective of social history, especially in the section From the town and surrounding areas.